HUBUNGAN GAYA BELAJAR DENGAN KOMPETENSI LITERASI NUMERASI SISWA DALAM KONTEKS BILANGAN PECAHAN DI SMP NEGERI 11 PONTIANAK - Bi'an, Rabi'an; Halini, Halini; Hamdani, Hamdani; R, Zubaidah; Siregar, Nurfadillah (Universitas Tanjungpura, 2024)
The students' poor literacy numeracy skills were the impetus for this study. Numeracy education abilities are vital in taking care of numerical issues in daily existence. One of the variables that can impact understudies' numeracy education abilities is acquiring style. There are three learning styles in this exploration, to be specific visual, hear-able and sensation. The purpose of this study is to determine whether students' numeracy literacy abilities are influenced by their visual, auditory, and kinesthetic learning styles. Quantitative correlation studies are the method of study. Information was gathered utilizing test, survey and interview procedures. The respondents in this examination were 33 understudies. Product Moment Correlation Analysis was used to test three hypotheses. The consequences of the examination show that visual learning style has a huge relationship with numeracy proficiency capacities with a connection coefficient of 0.861, hear-able learning style has a critical relationship with numeracy education capacities with a relationship coefficient of 0.806 and sensation has a critical relationship with numeracy proficiency capacities. education capacity with a relationship coefficient of 0.649. Subsequently, it tends to be presumed that the higher the learning style an understudy has, the higher the understudy's numeracy proficiency capacity.